The Relationship Between Information Exposure And Education Level to Self-Awareness Knowledge SADARI in Women of Childbearing Age - Marlynda Happy Nurmalita Sari; Endang Sundari (Journal of Midwifery Science: Basic and Applied Research, 2022)
Breast cancer is the main cause of death in women. The prevalence of cancer in West Java is still relatively high. In Bekasi City, there has been an increase in the presentation of breast cancer in women aged 30-50 years from 77 people (1.85%) in 2017 to 91 people (4.18%) in 2018. This is due to a lack of knowledge and awareness of doing Breast Self-Examination (BSE) to prevent breast cancer. The research objective was to find out the relationship between information exposure and education level on BSE knowledge in WUS at the Endang Sundari Midwife Independent Practice Center in Bekasi 2022. This research used a descriptive design with a cross-sectional design, a sample size of 123 respondents. The sample used used the inclusion criteria, namely not being pregnant or breastfeeding, being able to read and write as well as the exclusion criteria of having breast cancer experience. The questionnaire used has been tested for validity and reliability. Using bivariate analysis with chi square test. The results showed that there was a relationship between information exposure (p-value 0.000 0.05) and level of education (p-value 0.000 0.05) with knowledge of women of childbearing age about BSE. This exposure to information and high education can increase BSE knowledge in women of childbearing age.